Non-rigid illusory contours and global shape transformations defined by spatiotemporal boundary formation - Erlikhman, Gennady; Xing, Yang Z.; Kellman, Philip J. (Frontiers in Human Neuroscience, 2014)
Spatiotemporal boundary formation (SBF) is the perception of form, global motion, and continuous boundaries from relations of discrete changes in local texture elements (Shipley & Kellman, 1994). In two experiments, small, circular texture elements underwent small displacements whenever an edge of an invisible (virtual) object passed over them. Unlike previous studies that examined only rigidly translating objects, we tested virtual objects whose properties changed continuously. Experiment 1 tested rigid objects that changed in orientation, scale, and velocity. Experiment 2 tested displays that transformed non-rigidly across a series of virtual object shapes. Results showed that robust SBF occurred for all of the rigid transformations tested, as well as for non-rigid virtual objects, producing the perception of continuously bounded, smoothly deforming shapes. These novel illusions involve perhaps the most extreme cases of visual perception of continuous boundaries and shape from minimal information. They show that SBF encompasses a wider range of illusory phenomena than previously understood, and they present substantial challenges for existing models of SBF.